APLIKASI MODEL SISTEM DINAMIS UNTUK ANALISIS FINANSIAL HUTAN RAKYAT KARET DI DESA PO’ONA - Massiri, Sudirman Daeng; Umar, Syukur; Baisa, Gisca (Universitas Tadulako, 2017)
This research aimed to arrange conceptual model of financial analysis of the community-rubber forest. This research was conducted in April- Jun 2017 in Po’ona village, Lembo Raya Sub district Morowali Utara district, Central Sulawesi Province. Data of this research was collected by interview with the farmers of a rubber forest, analysed with financial analysis, with applied a dynamic system model. This research applied the program of Stella in arranging the dynamic system model of financial analysis of the community-rubber forest. The result of this study showed that system dynamic model was able to be applied in financial analysis of community - rubber forest. Based on this analysis, the community-rubber forest is feasible to be developed in Po’ona Village with the interest rate of 14%, because it generates NPV greater than 1. The NPV of community – rubber forest in Po’ona Villege with the interest rate of 14% was 72.408.918,46 IDR/Ha. Conceptual model of financial analysis of community-rubber forest could be applied for financial analysing the others of community – rubber forest.